Coffee and tea consumption and the risk of head and neck cancer: an updated pooled analysis in the International Head and Neck Cancer Epidemiology Consortium - Nguyen, Timothy; Koric, Alzina; Chang, Chun-Pin Esther; Barul, Christine; Radoi, Loredana; Serraino, Diego; Purdue, Mark P.; Kelsey, Karl T.; McClean, Michael D.; Negri, Eva; Edefonti, Valeria; Moysich, Kirsten; et al. (Cancer, 2024)
Introduction The relations between coffee and tea consumption and head and neck cancer (HNC) incidence are unclear. With increasing global HNC burden, this study aims to examine the association between coffee, tea, and HNC. Methods A pooled analysis of 9548 HNC cases and 15,783 controls from 14 individual-level case-control studies was conducted from the International Head and Neck Cancer Epidemiology consortium. Random-effects logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for HNC and its subsites, adjusting for sociodemographic and lifestyle factors. Results Compared to non-coffee drinkers, drinking >4 cups of caffeinated coffee daily was inversely associated with HNC (OR, 0.83; 95% CI, 0.69-1.00), oral cavity (OR, 0.70; 95% CI, 0.55-0.89), and oropharyngeal cancers (OR, 0.78; 95% CI, 0.61-0.99). Drinking 3-4 cups of caffeinated coffee was inversely associated with hypopharyngeal cancer (OR, 0.59; 95% CI, 0.39-0.91). Drinking decaffeinated coffee and drinking between >0 to <1 cup daily were inversely associated with oral cavity cancer (OR, 0.75; 95% CI, 0.64-0.87 and OR, 0.66; 95% CI, 0.54-0.81). Drinking tea was inversely associated with hypopharyngeal cancer (OR, 0.71; 95% CI, 0.59-0.87). Daily tea consumption of >0 to ≤1 cup was inversely associated with HNC (OR, 0.91; 95% CI, 0.84-0.98) and hypopharyngeal cancer (OR, 0.73; 95% CI, 0.59-0.91), but drinking >1 cup was associated with laryngeal cancer (OR, 1.38; 95% CI, 1.09-1.74). Conclusion These findings support reduced HNC risk among coffee and tea drinkers. Future studies are needed to address geographical differences in types of coffee and tea to improve our understanding of the association of coffee and tea and global HNC risk.